Shamans and Confucian Public Officials: Religion and Social Recognition in Korea - Doménech del Río, Antonio J. (’Ilu. Revista de Ciencias de las Religiones, 2019)
Relations between different religious and philosophical traditions in the Korean Peninsula have gone through periods of harmonious coexistence and other more conflictive ones throughout its history. An important moment of change between a pluralistic society and a society increasingly focused on Confucian thought was during the Goryeo kingdom (918-1392). The purpose of this article is to show how social changes influence the social recognition of shamanism practices and practitioners in Korea, especially in relation to Confucian public officials. To illustrate these social changes and their influence on the social recognition of the religious practitioner, I will analyse a text that reflects them. The text, which has not previously been translated into Spanish, is a poem by the Confucian scholar Yi Gyubo (1168-1241), Nomupyeon (Lay of the Old Shaman), where we can see well the relationship between the shamans and the Confucian officials during the second half of the Goryeo dynasty. This poem shows the social and political changes that took place in society at this time and how religious practices play an important role in power struggles. The position of shamans in society was changing as the new social, philosophical and religious ideas of Neo-Confucianism were established and spread across the Korean peninsula. In a parallel process, shamanism will become a practice associated with women, with all implications that this means in terms of gender values. These changes will influence the position of the shamans and their recognition by society from then until today in Korea.